The Pachynidae fam. nov. (Crustacea: Amphipoda: Lysianassoidea) - Lowry, J. K.; Stoddart, H. E. (Zootaxa, 2012)
The new family Pachynidae is established. Three new genera are described: Renella gen. nov., Smaraldia gen. nov. andUltimachelium gen. nov. and fifteen new species: Drummondia marlo sp. nov., D. tridentata sp. nov., Figorella angulosasp. nov., F. formosa sp. nov., F. franklin sp. nov., Pachychelium tropicalis sp. nov., Pachynus obsolescens sp. nov. andSmaraldia springthorpei sp. nov. from Australian waters; Ekelofia eltanin sp. nov. from Antarctic waters; Prachynellashijiki sp. nov. from Japanese waters; Pachychelium fucaensis sp. nov. from south-western Canadian and Californian wa-ters; Prachynella epa sp. nov. and Pr. oculata sp. nov. from Californian waters; and Drummondia luce sp. nov. and Ulti-machelium tac sp. nov. from southern Chilean waters. New records of Pachynus barnardi Hurley, 1963 and Prachynellalodo J.L. Barnard, 1964 are reported from Canadian waters; Drummondia corinellae Lowry, 1984, Figorella tasmanicaLowry, 1984, Pachynus denticulatum Lowry, 1984, P. pugilator Lowry, 1984, Sheardella kapala Lowry, 1984 and S. tan-garoa Lowry, 1984 from Australian waters; and Renella sculptidentata (Ren, 1991), Ultimachelium nichollsi (Lowry, 1984) and U. schellenbergi (Lowry, 1984) from Antarctic waters.